PENGARUH KOMUNIKASI DAN KERJA SAMA TIM TERHADAP KINERJA KARYAWAN PADA PT. AMAAN INDONESIA SEJAHTERA CABANG BOGOR 3 - Reva Walda; Irwansyah (Journal of Research and Publication Innovation, 2025)
This study aims to analyze the effect of communication and teamwork on employee performance at PT Amaan Indonesia Sejahtera. Effective communication and solid teamwork are believed to improve overall employee performance. According to (Kamaluddin et al.: 2023), it shows that communication has a positive effect on performance, both in the context of interpersonal communication and good teamwork. Then (Hamiruddin et al.: 2019) added that teamwork is a group of individuals who work together to achieve the same goal. Meanwhile, (Hasibuan: 2019) showed that effective collaboration increases efficiency and innovation which has a positive impact on performance. The research method used is quantitative with a descriptive approach, by distributing questionnaires to 52 employees at PT Amaan Indonesia Sejahtera. The research sample was taken randomly from the employee population of the Bogor Branch company. The data collected was analyzed using multiple regression methods, to test the relationship between Communication and Teamwork on Employee Performance. The results of the analysis show that good communication has an impact on improving employee performance with the results of the t-test value of 11.992> t table 2.010 with a significance of 0.000<0.05. Teamwork also has a positive effect on employee performance with the value of the t-test of 9.082> t table 2.010 with a significance of 0.000<0.05. The correlation coefficient (R) value of 0.871 indicates a strong relationship between communication and teamwork on employee performance. With a determination coefficient value (R²) of 76%, which means that variations in employee performance can be explained by communication and teamwork. In addition, the results of the F test show a calculated f value of 77.153> f table value of 3.19 with a significance of 0.000<0.05, this proves that the regression model used is significant. This means that there is a positive and significant influence simultaneously between communication and teamwork on employee performance at PT Amaan Indonesia Sejahtera. The conclusion of this study is that communication and teamwork are important factors in improving employee performance.